Substitution of commercial concentrate with soy bean meal protected by tannin from banana stem juice for lambs - Dwi Yulistiani; I-W. Mathius; W. Puastuti (Jurnal Ilmu Ternak dan Veteriner, 2011)
Study was conducted to evaluate the optimal utilization of protected soy bean meal with secondary compound from banana stem juice in ration for sheep and its effect on sheep performance. Soy bean meal was mixed with banana stem juice at ratio 1:1 (w/v) then dried in the oven at temperature 90oC. This protected soy bean meal was used to substitute commercial concentrate in sheep ration. The experiment used 24 head male lamb Sumatera composite breed. The lambs were grouped into six group based on its body weight and was assigned to one of 4 diets treatment. The sheep was fed on grass basal diet and supplemented with commercial concentrate. Data recorded were feed consumption, nutrient digestibility, average daily gain, feed efficiency and nitrogen utilization. Study was conducted in randomized complete block design and data obtained were analyzed using general linier model from SAS program.  Results show that dry matter intake (DMI) significantly (P < 0.05) increased with concentrate substitution by protected soy bean meal, however, there was no significant different (P > 0.05) between R10, R20 and R30. The increasing in DMI is followed by the increasing crude protein (CP) from 8.75 (R0) to 10.64; 11.68 and 12.32 g/BB0.75 respectively for R10; R20 and R30. Commercial concentrate substitution by protected soy bean meal significantly increased DM and CP digestibility at all levels. However, this substitution did not significantly affected organic matter (OM), neutral detergent fiber (NDF) and acid detergent fiber (ADF) digestibility. Nitrogen excretion in urine was only increased at this level 30% substitution but nitrogen retention increased at substitution levels 20 and 30%. From this study can be concluded that commercial concentrate substitution with protected soy bean meal in the diet only increased CP consumption and CP digestibility but not average daily gain of lamb. Key Words: Soy Bean Meal, Tannin, Protein, Banana Stem Juice